Survey of Physical Fitness Levels Among 7th Grade Students at SMPN 16 Jambi City (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Physical fitness is defined as an individual's physical capability to perform daily physical tasks optimally and still be able to carry out additional physical activities without experiencing significant fatigue. The research method employed in this study is a quantitative descriptive approach using a survey method. This research involved 80 students, consisting of 30 males and 50 females. The data collection technique utilized the TKJI (Indonesian Physical Fitness Test), which is a series of tests; therefore, all test items must be carried out sequentially, continuously, and without interruption, with attention to speed. The transition from one test item to the next is within 3 minutes.The research findings indicate that the physical fitness level of male students is dominated by the average to below-average categories, with 40% in the average category and 60% in the below-average category, with a mean score of 13.03 points. Meanwhile, the majority of female students fall into the average (6%) and below-average (88%) categories, with a mean score of 11.32 points. Analysis per indicator shows that for male students, the 50-meter sprint speed is relatively good, with 70% in the good and excellent categories. However, the 1000-meter run endurance is very low, with 76.7% in the below-average category and 23.3% in the poor category